Peritoneal dialysis patient selection from a comorbidity perspective. Issue 1 (22nd October 2020) - Eroglu, Eray; Heimbürger, Olof; Lindholm, Bengt
Abstract: Despite many medical and socioeconomic advantages, peritoneal dialysis (PD) is an underutilized dialysis modality that in most countries is used by only 5%–20% of dialysis patients, while the vast majority are treated with in‐center hemodialysis. Several factors may explain this paradox, such as lack of experience and infrastructure for training and monitoring of PD patients, organizational issues, overcapacity of hemodialysis facilities, and lack of economic incentives for dialysis centers to use PD instead of HD. In addition, medical conditions that are perceived (rightly or wrongly) as contraindications to PD represent barriers for the use of PD because of their purported potential negative impact on clinical outcomes in patients starting PD. While there are few absolute contraindications to PD, high age, comorbidities such as diabetes mellitus, obesity, polycystic kidney disease, heart failure, and previous history of abdominal surgery and renal allograft failure, may be seen (rightly or wrongly) as relative contraindications and thus barriers to initiation of PD. In this brief review, we discuss how the presence of these conditions may influence the strategy of selecting patients for PD, focusing on measures that can be taken to overcome potential problems.